Marketing strategy with marketing mix for Lake Toba tourism destination - Kennedy, Posma Sariguna Johnson; Tobing, Suzanna Josephine L.; Lumbantoruan, Rutman (Goodwood Publishing, 2022)
Purpose: This study aims to identify effective and targeted policy strategies to improve the quality of Lake Toba. Lake Toba, a popular tourist destination in Indonesia, faces global competition and needs continuous development to maintain its appeal to domestic and international travelers. This study incorporates marketing mix policy theory to guide the design of these strategies. Objective: The objective of this study is to identify effective and targeted policy strategies to improve the quality of Lake Toba, a popular tourist destination in Indonesia. Scope: The scope of this study includes various aspects related to marketing strategy and marketing mix in the context of Lake Toba as a tourist destination. Research Methodology: Qualitative research included field studies, stakeholder interviews, and secondary data analysis. Results: This study provides a comprehensive marketing strategy for the Lake Toba tourism area that encompasses positioning, market analysis, product development, market penetration, and market development. Limitations: The strategy discussed in this study concerns a marketing strategy in which the marketing mix is included. Contributions: The results and recommendations of this study will be valuable for local governments, tourism entrepreneurs, and communities involved in addressing challenges and improving the tourism sector in the Lake Toba area. Novelty: This study explores the development of appropriate marketing strategies to promote Lake Toba as a tourist destination.